TA’LIMDA SIFATLI BAHOLASH: O‘Z-O‘ZINI BAHOLASH VA NOSTANDART YONDASHUVLAR - Meyliyeva, N.G. (SCIENCE and SOCIETY, 2025)
The article analyzes assessment processes in the education system through the lens of innovative approaches. It discusses the importance of developing human capital, teachers' self-assessment, and non-traditional assessment methods. Modern assessment methodologies for quality education are presented, including ipsative and feedback assessments. Based on Benjamin Bloom's taxonomy, the article explores opportunities for enhancing the effectiveness of the educational process. The aim of the article is to implement quality changes in the education sector, to continually analyze teachers' activities, and to introduce innovative approaches. It also emphasizes that these processes are significant not only for personal development but also for the advancement of society and the country as a whole.
Keywords: education; assessment; human capital; quality; pedagogue; self-assessment; non-standard assessment; ipsative assessment; feedback; innovative approach; Benjamin Bloom; taxonomy; educational process; efficiency; development